Business Strategy Formulation : A Literature Review - Risdarwanto; Nasution, Harmein; Pujangkoro, Sugiharto (Jurnal Sistem Teknik Industri, 2023)
Strategy is a series of actions that are formulated to achieve long-term goals by involving resources to achieve competitive advantage. Strategy formulation  to develop the business must be adjusted to the wishes of consumers to achieve competitive advantage. Business strategy focuses on growth and profitability by providing a framework for functional and operational strategies in terms of which products should be developed, how they should be priced and distributed, as well as which market segments should be targeted. The strategy formulation is determined in three steps consisting of: input step, matching step and decision-making step. The input step focuses for analyzing Company’s Internal and External Factor. The matching step focuses for determining strategies based on Company’s Internal and External Factor by using  SWOT, SPACE and BCG Matrix.  Decision step focuses for determining the best strategy using the Quantitave Strategic Planning Matrix (QSPM). This paper aims to review several studies that use formulation strategy methods in making the best decisions for companies. Without being based on a formulation strategy, it is very difficult for companies in making the best decisions to achieve competitive advantage